Human enteric viruses’ detection in mussels (Mytilus galloprovincialis) farmed in the central Adriatic Sea - Gianluigi Ferri; Vincenzo Olivieri; Alberto Vergara (Italian Journal of Food Safety, 2024)
Human enteric viruses, such as hepatitis A virus (HAV), hepatitis E virus (HEV), and norovirus genogroups I and II (NoVGI and NoVGII), cause infections, and it has been largely demonstrated that mussels play an important role if consumed as raw or undercooked food matrices. This study aimed to investigate, through qualitative and quantitative biomolecular assays, the detection of partial genomic regions belonging to the most relevant enteropathogenic viruses for humans (HAV, HEV, NoVGI and NoVGII) in mussels (Mytilus galloprovincialis) farmed along the coasts of two Italian regions on the central Adriatic Sea: Abruzzo (Casalbordino, Chieti) and Molise (Termoli, Campobasso). A total of 425 animals were sampled, and the respective georeferentiations were registered. A total of 85 pools, each composed of five subjects/aliquot, were formed (22 from Abruzzo and 63 from Molise regions). This step was followed by homogenization and RNA extraction, and then the biomolecular assays [nested reverse transcription polymerase chain reaction (PCR) and real-time reverse transcription-quantitative PCR] were performed. 1.17% of the pool was positive for HAV RNA detection (102 copies/mL), 9.41% for HEV (102-103 copies/mL), 2.35% for NoVGI (101 copies/mL), and no pool was positive for NoVGII. This study demonstrated the human enteric viruses’ presence in mussels farmed in a low-investigated marine area. Based on a one-health point of view, this paper wants to enforce the importance of biomolecular and epidemiological screenings as surveillance systems to guarantee human, animal, and environmental health.